Pengaruh Media Pembelajaran Digital ( Kamus Digital) Terhadap Hasil Belajar Bahasa Indonesia Siswa kelas IV SD - Nur Azmi Alwi; Nurul Halimah; Marnis Susanti; Lina Marcelina (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The purpose of this study was to find out whether there was a significant difference between the learning outcomes of fourth grade Indonesian elementary school students who used digital teaching materials (digital dictionary) and those who used traditional teaching materials. The method used is an experimental strategy using a post-test only control group design. This research tool uses a test and non-test methodology. To test the data, descriptive and inferential statistics were used. The results showed that the t count exceeds the t table by 6.168 based on the results of the t test analysis. This shows that there is a significant difference between the learning outcomes of Indonesians who use digital teaching materials (such as digital dictionaries) and Indonesians who use traditional teaching materials.